EVALUATING POLICY EFFECTIVENESS ON COASTAL MANGROVE MANAGEMENT: CASE STUDY IN KIEN THUY AND DO SON DISTRICTS, HAI PHONG CITY - Nguyet Anh, Nguyen; Hai Hoa, Nguyen (Journal of Forestry Science and Technology, 2017)
This study aims to investigate relevant policies in study site from 1990 to 2016 using multi-temporal Landsat images; to assess the effectiveness of policies on coastal mangrove management using three major indicators; and then to propose feasible solutions to enhance the policies in this area. Three remarkable policy periods have been investigated and assessed by using a set of three significant indicators, including ecological, economic and social indicators. As a result, from 1990 - 1997, mangrove rehabilitation and restoration projects had been implemented, but they were not effective. From 1997 - 2005, the implementation of many policies and projects had improved the quantity and quality of mangroves. Hence, the increase of mangrove extent considerably contributed to local incomes and livelihoods improvement. The period from 2005 to 2016 has been well-known as mangrove development and protection stage. This study also suggests that the communes should adapt communities - based management (CBM) to enhance the mangrove quantity and quality in the long term.